Analisis Kompetensi Pedagogik dan Profesional Mahasiswa Praktek Pengalaman Lapangan Madiri (PPLM) Program Studi Pendidikan Teknik Informatika dan Komputer (PTIK) IAIN Bukittinggi - Ahmad Dori Pelita Ansara; M. Yemmardotillah (Continuous Education: Journal of Science and Research, 2022)
The PPL is a network of programmed activities for the LPTK students, which includes both teaching and training outside of teaching. It is a ground for shaping and developing the professional competence required by the work of a teacher or other educational institution. The aim is for the personality of the prospective educator who has the necessary body of knowledge, skill, value and attitude, as well as the pattern of conduct for his profession and is able and properly employed in conducting education and teaching. The practice of self-field experiences (PPLM) is a form of practical experience for tarbiyah and teacher trainig faculty students, in order to adjust between the theories acquired on the college bench and its practices at pademi covid-19. As for the main objectives of student PPL were able to instill teacher competence as professional candidates. Due to changes from PPL to PPLM, the research will be initiated to analysis of pedagogical competence and the professional competence of the student students who carry out PPLM activities. As for the methods used in this research are quantitative and potent sampling methods. The study is done in information and computer engineering education departments IAIN Bukittinggi.